Ten-years outcome analysis in patients with clinically localized prostate cancer treated by radical prostatectomy or external beam radiation therapy - Li, Shu-Wen; Chiu, Allen W.; Huang, Andy C.; Lai, Yu-Wei; Leu, Jyh-Der; Hsiao, Yi-Chun; Chen, Shiou-Sheng; Hsueh, Thomas Y. (Frontiers in Surgery, 2022)
Purpose: Since there was no consensus on treatment options for localized prostate cancer, we performed a retrospective study to compare the long-term survival benefit of radiotherapy (RT) versus laparoscopic radical prostatectomy (LRP) in Taiwan. Methods: 218 patients with clinically localized prostate cancer treated between 2008 and 2017 (64 with LRP and 154 with RT) were enrolled in this study. The outcomes of RT and LRP were assessed after patients were stratified according to Gleason score, stage, and risk group. Crude survival, prostate cancer-specific survival, and metastasis-free survival were evaluated using the log-rank test. Results: The 5-year crude survival rate was 93.3% in the LRP group and 59.3% in the RT group. A significant survival benefit was found in the LRP group compared with the RT group (p = 0.004). Furthermore, significant differences were found in disease-specific survival (93.3% vs. 64.7%, p = 0.022) and metastasis-free survival (48% vs 40.2%, p = 0.045) between the LRP and RT groups. Conclusions: Men with localized prostate cancer treated initially with LRP had a lower risk of prostate cancer-specific death and metastases compared with those treated with RT.